Exploring smartphone utilization patterns, addiction, and associated factors in school-going adolescents: A mixed-method study - Hemangi M. Ladani; M Yogesh; Nidhi S. Trivedi; Rohankumar B. Gandhi; Dhruv Lakkad (Journal of Family Medicine and Primary Care)
Background: Smartphone use and addiction among adolescents is an emerging public health concern. This study aimed to assess smartphone use, addiction, patterns of use, and associated factors among adolescents. Methods: An institutional-based mixed-method study was conducted among 560 adolescents aged 15–19 years. Data were collected on smartphone use, and addiction assessed by a Short Version of the Smartphone Addiction Scale (SAS-SV), patterns of use, and correlations with demographic factors, physical health, and psychological symptoms. Statistical analysis included percentages, logistic regression, and tests of significance. A P value of < 0.05 is considered significant. Results: Smartphone use prevalence was 89.8% [95% CI (87.09%–92.49%)], and addiction prevalence was 64% [95% CI (62.66%–72.34%)] among users. Factors associated with smartphone use are statistically significant based on adjusted odds ratios (AOR), which were urban residence [2.5 (1.8–3.8)], use of handsfree kit [2.04 (1.56–2.95)], illiterate father’s education [2.7 (1.9–7.8)], illiterate [2.38 (1.98–5.7)], primary/secondary educated [2.15 (1.06–4.3)] mother’s education, and addiction [3.2 (1.7–4.3)]. Addicted users showed higher use for gaming, videos, and social media (P < 0.05). No significant physical or psychological health differences were found between addicted and non-addicted groups. Conclusions: Smartphone addiction (SA) was highly prevalent among adolescents. Use patterns, such as gaming and social media, as well as perceptions of harm, were implicated in addiction risk. Tailored interventions are required to address this emerging public health problem among adolescents.